TINGKAT KEBUGARAN JASMANI ANGGOTA KLUB JANTUNG SEHAT (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The research problem how is the level of physical fitness in healthy heart club Mugas Semarang City Year2013. The purpose of the study was to describe the level of physical fitness in healthy heart club MugasSemarang City Year 2013. The method used is an experimental method to form a one-shot case study (onetimetreatment / treatment). Based on the results of this study concluded that the level of physical fitness inhealthy heart club Mugas Semarang City Year 2013 mostly in the category of less than once with a percentageof 45%. Cause of the results of this research because of the frequency of exercise, intensity of exercise and weightloss, and nutrition. Suggestions are: 1) the need for the implementation of physical activity through sportsactivities are more weighty and appropriate skills for the members of the club, 2) The management of the cluband the coach can provide a structured program and variarif.